Synergizing Digital Transformation and Human Capital: Pathways to Competitive Advantage and Sustainable Growth - Hanoeboen, Bin Raudha Arif; Kurniawan, Sabda Aji; Ningsih, Nadya Nurlailya; Yusuf T, Glen Andre (International Ecsis Association, 2025)
In the era of digital economy acceleration, micro, small, and medium enterprises (MSMEs) face increasing pressure to sustain competitiveness amid dynamic technological and market transformations. For culinary MSMEs in Ambon, digital transformation and human capital quality have become decisive factors in ensuring business resilience and sustainable growth. This study aims to examine the effects of digital transformation and human resource quality on competitive advantage and MSME competitiveness, and their subsequent implications for sustainable economic growth. It also seeks to identify the mediating role of competitive advantage in linking organizational capabilities with long-term sustainability outcomes. A quantitative explanatory approach was employed using data from 63 culinary MSME owners collected through structured questionnaires and analyzed with Partial Least Squares (SmartPLS 4.0). The results demonstrate that digital transformation significantly enhances competitive advantage through efficiency optimization and innovation, while human resource quality serves as a complementary strategic driver. Competitive advantage strongly influences MSME competitiveness, which subsequently contributes to inclusive and sustainable economic growth. The findings underscore that integrating digital technology with skilled human resources is essential for strengthening MSME competitiveness and regional economic resilience. Theoretically, this study extends the Resource-Based View by positioning digital transformation and human capital as synergistic capabilities. Practically, it provides actionable insights for policymakers and business stakeholders to design digital training programs and ecosystem support for MSMEs’ sustainable advancement.